Loosely Sutured: a reflective practice memoir of a ‘white' art educator’s journey into the impossibilities and possibilities of 'white' anti-racist research in art and design education. - Trowell, Jane (2025)
This research is into the formation and disruption of racism, coloniality and whiteness in 'white' art educators, including those who identify as anti-racist such as the author. The researcher is a 'white' middle-class female art educator operating within an activist paradigm of social justice practice in art and design education. The research was conducted in the UK during an era of heightened inequity, fuelled by populism, government-led racism and xenophobia, and draconian cuts across arts education in England from early years to higher education.